Situation Report: Albania, 18 April 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Radio Moscow on Soviet-Albanian Friendship Albanian Commentary on Chou En-Lai [Enlai Zhou] Report Tirana Attacks Parliamentary Road to Socialism Albania Attacked at Komsomol Congress Albania Restored to May Day List